Penerapan Logika Fuzzy untuk Meningkatkan Efisiensi Pengembangbiakan Maggot Berbasis IoT - Pratama, Novaly Arya; Sutrisno, Imam; Rinanto, Noorman (Jurnal Elektronika dan Otomasi Industri, 2024)
The 3R Waste Disposal Site "REJOAGUNG BERSERI" in Rejoagung Village is facing household waste management issues, particularly with organic waste contaminating the environment. The proposed solution is cultivating maggots (black soldier fly larvae) using organic waste. The challenges in maggot cultivation include natural predators, non-ideal environmental conditions, and a sensitive life cycle. Maggots are a high-protein feed source for livestock, containing 42% protein and possessing antimicrobial properties. In this research, we propose a monitoring and control system for maggot cultivation based on fuzzy logic in an IoT implementation to improve the efficiency of maggot cultivation. This system will optimize environmental conditions based on IoT sensor data such as temperature, humidity, and light intensity, thereby enhancing the quality and quantity of maggot production.